Fetal neural tube defects in pregnant women previously submitted to bariatric surgery: more attention to a new emerging entity. (6th December 2012) - Pelizzo, Gloria; Nakib, Ghassan; Alfei, Alessandro; Iasci, Angela; Cena, Hellas; Locatelli, Davide; Mosconi, Mario; Zappoli, Federico; Calcaterra, Valeria
<x xml:space="preserve">Abstract</x> What's already known about this topic? The pathogenesis of neural tube defects is multifactorial. What does this study add? Although the pathogenesis of neural tube defects is certainly multifactorial, malnutrition after bariatric surgery has to be considered a major risk factor. Women who have undergone bariatric procedure must receive nutritional counselling before and after conception.